Genome mining for production of nutritionally rich palm oil - Abdullah, Siti Nor Akmar; Babura, Sulaiman Rufai; Kong, Sze Ling; Munusamy, Umaiyal; Marjuni, Marhalil; Amiruddin, Mohd Din (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
The vitamin E in palm oil contains high proportion of tocotrienol (70% tocotrienols and 30% tocopherols) while most other vegetable oils contain only tocopherols. Both tocopherols and tocotrienols are strong chain-breaking antioxidants. The interest in tocotrienols escalated when the other medicinal properties such as neuroprotective, anticancer and cholestrol-lowering were discovered. This report is based on studies carried out on the different vitamin E biosynthetic pathway genes in order to understand their molecular regulatory mechanism in the two important oil palm species, E. guineensis and E. oleifera. The expression profiles of the different genes correlate with oil accumulation period in the fruit mesocarp suggesting the pivotal role of vitamin E in maintaining oxidative stability of the oil. The presence of a set of common regulatory elements in the promoters of these genes indicate that the pathway is coordinately control by endogenous and environmental cues at the transcriptionl level. PCR-based SNP markers for routine screening of the oil palm breeding materials were developed using mismatch primers. Some of the innovative approaches used in our laboratory for functional studies to know the effects of sequence variants on the function of the vitamin E biosynthetic genes are described.